Samenwerking met sendinggenootskappe: ’n Perspektief vanuit die Ned Geref Kerk - Meiring, P.G.J. (Acta Theologica, 2022)
The article focuses on the sometimes strained relationships between mission societies and the churches. Within the ranks of the Ned Geref Kerk (DRC), too, there were those who worked under the auspices of societies, while others stressed the importance of the mission of the church. Reasons for the re-establishment of better relations the past years, are discussed.